PERBAIKAN INSTALASI AIR BERSIH DAN PERGANTIAN MESIN POMPA AIR UMUM MASYARAKAT NAGORI SILABAH JAYA (GAMBIRI) KABUPATEN SIMALUNGUN - Pramadya Ragatna Silalahi; Tintoni Ray Saragih; Hartiv Malum Manurung; Daniel Tony E Siburian (Abdi Jurnal Publikasi, 2025)
Water is a basic human need that is used for drinking water, bathing, washing and so on. The main problem is inadequate air distribution due to damaged air installations, so that it can disrupt daily community activities. The solution offered is to restore the water installation in Silabah Jaya Village. The method used is a participatory approach, survey. The purpose of this repair is to ensure the availability of sufficient water for the life of hamlet 2 of Silabah Jaya Village. KPPM activities have succeeded in repairing clean water pipe installations and replacing water pump machines to meet the availability of clean water that can support activities and meet community needs.